The Influence Of Promotion, Interest Rates, And Service Quality On Customer Satisfaction At Bak Perkreditan Rakyat (BPR) Dana Nusantara Kc Sp Plaza Batam - Sinaga , Gideon Romula; Dabur , Feliks; Harianja, Josepin (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This study aims to determine the effect of promotions, credit interest rates and services either partially or simultaneously on customer satisfaction at the People's Credit Bank (BPR) Dana Nusantara in KC SP Plaza Batam. This research was conducted using quantitative research methods with a total of 109 respondents and data collection using a questionnaire. The results of this study found that tcount was 4.648 > ttable was 1.659 with a significantce level of 0.00 <0.05, so the of promotion had positif a significant and significantce effect on customer satisfaction. tcount of 1.198 < ttable of 1.659 with a significantce level of 0.234 <0.05, then credit interest rates have no positif and insignificant effect on tcount of 3.538 > ttable 1.659 with a significantce level of 0.001 <0.05, then service has a positif and significant effect on customer satisfaction. From the F test it is known that the fcount of promotions, credit interest rates, and services is 120.688 > 2.69 ftable with a significantce value of 0.000 <0.05. This shows that the variabel. promotion, interest rates, and services simultaneously have a positif and significant effect on customer satisfaction at the People's Credit Bank (BPR) Dana Nusantara KC SP Plaza Batam. Keywords: Promotion, Credit Interest rates, service quality and customer satifaction